Foxa2 and Pdx1 cooperatively regulate postnatal maturation of pancreatic β-cells - Aimée Bastidas-Ponce; Sara S. Roscioni; Ingo Burtscher; Erik Bader; Michael Sterr; Mostafa Bakhti; Heiko Lickert (Elsevier, 2017)
Objective: The transcription factors (TF) Foxa2 and Pdx1 are key regulators of beta-cell (β-cell) development and function. Mutations of these TFs or their respective cis-regulatory consensus binding sites have been linked to maturity diabetes of the young (MODY), pancreas agenesis, or diabetes susceptibility in human. Although Foxa2 has been shown to directly regulate Pdx1 expression during mouse embryonic development, the impact of this gene regulatory interaction on postnatal β-cell maturation remains obscure. Methods: In order to easily monitor the expression domains of Foxa2 and Pdx1 and analyze their functional interconnection, we generated a novel double knock-in homozygous (FVFPBFDHom) fluorescent reporter mouse model by crossing the previously described Foxa2-Venus fusion (FVF) with the newly generated Pdx1-BFP (blue fluorescent protein) fusion (PBF) mice. Results: Although adult PBF homozygous animals exhibited a reduction in expression levels of Pdx1, they are normoglycemic. On the contrary, despite normal pancreas and endocrine development, the FVFPBFDHom reporter male animals developed hyperglycemia at weaning age and displayed a reduction in Pdx1 levels in islets, which coincided with alterations in β-cell number and islet architecture. The failure to establish mature β-cells resulted in loss of β-cell identity and trans-differentiation towards other endocrine cell fates. Further analysis suggested that Foxa2 and Pdx1 genetically and functionally cooperate to regulate maturation of adult β-cells. Conclusions: Our data show that the maturation of pancreatic β-cells requires the cooperative function of Foxa2 and Pdx1. Understanding the postnatal gene regulatory network of β-cell maturation will help to decipher pathomechanisms of diabetes and identify triggers to regenerate dedifferentiated β-cell mass. Keywords: Foxa2, Pdx1, β-Cell maturation, β-Cell identity, Trans-differentiation